Experimental study on freeze–thaw damage characteristics of coal samples of different moisture contents in liquid nitrogen - Xiaoqi Wang; Xiaohan Qi; Heng Ma; Ke Gao; Shengnan Li (Scientific Reports, 2022)
Abstract In this study, the surface crack-propagation law and pore damage characteristics of coal samples of different water contents after they undergo leaching in liquid nitrogen are investigated using a 4 K scientific-research camera, HC-U7 non-metal ultrasonic detector, nuclear magnetic resonance testing technology, and self-made multi-functional three axial fluid–solid coupling test system. Experimental investigations are conducted on coal samples of different water contents before and after they undergo liquid-nitrogen freezing and thawing in order to determine the propagation law of surface fissures, the development law of internal micro-fissures, the development process of internal pores, the change law of the pore-size distribution, and the law of coal-sample deformation and gas seepage during the stress process. The test results show that, with the increase in water content in the liquid-nitrogen leaching process, the frost heave force on the coal surface increases, and the greater the increase ratio of the coal porosity, the faster is the development of micro-cracks and pores. Under the action of liquid nitrogen, the number of micro-pores, meso-pores, and macro-pores in the coal sample increased, and with the formation of new cracks and the connection of the original cracks, liquid-nitrogen freezing and thawing can promote the development of the pore structure in the coal body. The permeability changes of coal samples of different water contents during unloading failure exhibit obvious stage characteristics. The above results demonstrate that the moisture content of coal has a significant effect on the development of surface cracks and pore-damage characteristics of coal after liquid-nitrogen freezing and thawing, and there is a positive correlation between the surface crack expansion and internal damage of the coal samples of different moisture contents leached in liquid nitrogen.